Synthesis of block functional mechatronic modules - Kryvoplias-Volodina, Liudmyla; Osmak, Alexei; Gavva, Oleksandr (My University, 2024)
The application of simulation software and computational resources in solving complex technical problems - creates an opportunity to integrate advanced technologies into new technical solutions. The review of pneumatic drives of vibration-inertial trays for transportation, separation into streams, reorientation of piece products has shown - that at present pneumatic muscles are used as actuators in tracking pneumatic systems with small displacements quite effectively. They have several advantages over pneumatic cylinders: absence of friction force and high forces at the same dimensions. Existing systems with the drive on pneumomuscules allow realizing motion frequencies up to 20 Hz. This fact allows at the first stage of design to calculate the designed platform by static parameters and to choose pneumatic cylinders with bellows housing (bellows pneumatic cylinders) as a replacement for muscles.

Застосування програмних засобів моделювання та обчислювальних ресурсів при вирішенні складних технічних задач - створює можливість інтеграції передових технологій в нові технічні рішення. Огляд пневмоприводів віброінерційних лотків для транспортування, розділення на потоки, переорієнтації штучних виробів показав, що на сьогоднішній день пневматичні м'язи досить ефективно використовуються в якості виконавчих механізмів в слідкуючих пневматичних системах з малими переміщеннями. Вони мають ряд переваг перед пневмоциліндрами: відсутність сили тертя і високі зусилля при тих же габаритах. Існуючі системи з приводом на пневмомускулах дозволяють реалізувати частоти руху до 20 Гц. Цей факт дозволяє на першому етапі проектування розрахувати проектовану платформу за статичними параметрами і вибрати пневмоциліндри з сильфонним корпусом (сильфонні пневмоциліндри) в якості заміни м'язів.
Keywords: кафедра мехатроніки та пакувальної техніки; pneumatic actuator; bellows cylinder; vibration; inertial platform; hysteresis; tracking control system; пневматичний привід; сильфонний циліндр; вібрація; інерційна платформа; гістерезис; система відстеження та контролю